Effect of epigenetic modification with trichostatin A and S-adenosylhomocysteine on developmental competence and POU5F1–EGFP expression of interspecies cloned embryos in dog. Issue 5 (October 2015) - Mousai, M.; Hosseini, S.M.; Hajian, M.; Jafarpour, F.; Asgari, V.; Forouzanfar, M.; Nasr-Esfahani, M.H.
Summary Adult canine fibroblasts stably transfected with either cytomegalovirus (CMV) or POU5F1 promoter-driven enhanced green fluorescent protein (EGFP) were used to investigate if pre-treatment of these donor cells with two epigenetic drugs [trichostatin A (TSA), or S-adenosylhomocysteine (SAH)] can improve the efficiency of interspecies somatic cell nuclear transfer (iSCNT). Fluorescence-activated cell sorting (FACS), analyses revealed that TSA, but not SAH, treatment of both transgenic and non-transgenic fibroblasts significantly increased acetylation levels compared with untreated relatives. The expression levels of Bcl2 and P53 were significantly affected in TSA-treated cells compared with untreated cells, whereas SAH treatment had no significant effect on cell apoptosis. Irrespective of epigenetic modification, dog/bovine iSCNT embryos had overall similar rates of cleavage and development to 8–16-cell and morula stages in non-transgenic groups. For transgenic reconstructed embryos, however, TSA and SAH could significantly improve development to 8–16-cell and morula stages compared with control. Even though, irrespective of cell transgenesis and epigenetic modification, none of the iSCNT embryos developed to the blastocyst stage. The iSCNT embryos carrying CMV–EGFP expressed EGFP at all developmental stages (2-cell, 4-cell, 8–16-cell, and morula) without mosaicism, while no POU5F1–EGFP signal was observed in any stage of developing iSCNT embryos irrespective of TSA/SAH epigenetic modifications. These results indicated that bovine oocytes partially remodel canine fibroblasts and that TSA and SAH have marginal beneficial effects on this process.